Tellurium-containing nanoparticles for controlled delivery of cisplatin based on coordination interaction. Issue 96 (3rd October 2016) - Cao, Wei; Li, Feng; Chen, Ruofan; Xu, Huaping
Abstract : Tellurium containing nanoparticles were designed and synthesized for the delivery of cisplatin. Abstract : Tellurium containing nanoparticles were designed and synthesized for the delivery of cisplatin based on coordination interaction. The tellurium containing nanomedicine could achieve better in vivo efficacy and reduce side effects, owing to the prolonged blood circulation. This kind of approach marked a new frontier of tellurium containing nanomedicine.